2010
DOI: 10.1007/s10096-010-1078-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the pathogen of diabetic toe osteomyelitis by two consecutive ulcer cultures with bone contact

Abstract: In this study, we investigate the accuracy of two consecutive ulcer cultures with bone contact compared to bone biopsy for the diagnosis of diabetic toe osteomyelitis. The same nurse and orthopaedic surgeon obtained all samples: sample A-1: bone contact swabbing through the ulcer; sample A-2: a second culture swabbing from the bone surface within 24 h; sample B: surgical bone biopsy in the operating theatre. The kappa statistic measure between samples A-1 and A-2 (bone contact swabs) indicated 82.35% agreement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…In particular, most studies with diabetic foot osteomyelitis have found that neither superficial nor deep soft tissue cultures correlate well with those of bone specimens . One study suggested, however, that repeated bone surface swabbing yields similar results compared with bone culture in patients with a wound with underlying clinical osteomyelitis , but this needs to be confirmed in larger trials.…”
Section: Definition and Classification Of Infectionmentioning
confidence: 97%
“…In particular, most studies with diabetic foot osteomyelitis have found that neither superficial nor deep soft tissue cultures correlate well with those of bone specimens . One study suggested, however, that repeated bone surface swabbing yields similar results compared with bone culture in patients with a wound with underlying clinical osteomyelitis , but this needs to be confirmed in larger trials.…”
Section: Definition and Classification Of Infectionmentioning
confidence: 97%
“…We collected samples for culture from pus or deep infected tissue, and did not accept results of cultures, superficial swab specimens or sinus tract. 10 The microbiology laboratory processed all specimens according to Clinical and Laboratory Standards Institute recommendations, 11 before they switched to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria in 2014. 12 We considered remission of DFI as the absence of any clinical, laboratory or imaging evidence of recurrence of the original infection.…”
Section: Definitionsmentioning
confidence: 99%
“…Diabetic foot infections (DFIs) [1][2][3] frequently require amputation, also because of concomitant ischaemia. In these cases, surgeons and physicians regularly debate the duration of post-amputation antibiotics, even in the absence of residual clinical signs of infection.…”
Section: Introductionmentioning
confidence: 99%